2013
DOI: 10.1038/bjc.2013.458
|View full text |Cite
|
Sign up to set email alerts
|

Critical weight loss is a major prognostic indicator for disease-specific survival in patients with head and neck cancer receiving radiotherapy

Abstract: Background:Pre-treatment weight loss (WL) is a prognostic indicator for overall survival (OS) in head and neck cancer (HNC) patients. This study investigates the association between WL before or during radiotherapy and disease-specific survival (DSS) in HNC patients.Methods:In 1340 newly diagnosed HNC patients, weight change was collected before and during (adjuvant) radiotherapy with curative intent. Critical WL during radiotherapy was defined as >5% WL during radiotherapy or >7.5% WL until week 12. Differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
195
3
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(213 citation statements)
references
References 37 publications
6
195
3
9
Order By: Relevance
“…По их данным, общая 5-летняя выживаемость в группе больных без нутритивной не-достаточности до и во время лечения равнялась 71 %; в тех случаях, когда потеря массы тела составляла от 5 до 10 %, общая 5-летняя выживаемость снижалась до 59 %, а при значительной потере (более 10 %) массы тела -не превышала 42 % (рис. 3) [13].…”
unclassified
See 1 more Smart Citation
“…По их данным, общая 5-летняя выживаемость в группе больных без нутритивной не-достаточности до и во время лечения равнялась 71 %; в тех случаях, когда потеря массы тела составляла от 5 до 10 %, общая 5-летняя выживаемость снижалась до 59 %, а при значительной потере (более 10 %) массы тела -не превышала 42 % (рис. 3) [13].…”
unclassified
“…Так, в группе больных с умеренной потерей массы тела 5-летняя безрецидивная выживаемость составила 89 % против 82 % у пациентов с выраженным дефицитом массы тела (рис. 4) [13]. При оценке влияния нутритивной поддержки на результаты хирургического лечения отмечается сходная тенденция.…”
unclassified
“…It has been associated with moderate-severe malnutrition and therefore is considered a simple valuable measure to use for this purpose (Attar et al, 2012). Significant weight loss has also been shown to negatively impact on patient and clinical outcomes, such as quality of life (Langius et al, 2013a) and survival (Langius et al, 2013b;Martin et al, 2015), and thus is a clinically significant measure readily available from retrospective data collection.…”
Section: Discussionmentioning
confidence: 99%
“…In a long-term follow-up study of their colorectal cohort -the patients with dietary counselling had better QOL and survival; with depleted nutritional intake/status predictive of shorter survival and late toxicity (Ravasco, Monteiro-Grillo, & Camilo, 2012). Meanwhile a study of HNC patients (n=1340), found weight loss was also a major prognostic indicator for survival (Langius et al, 2013b). The study reported >10% weight loss pre-treatment was associated with worse overall survival and disease-specific survival.…”
Section: Consequences Of Malnutritionmentioning
confidence: 99%
See 1 more Smart Citation